Pengembangan Buku Non Teks Bertema Nilai-Nilai Karakter pada Relief Monumen Simpang Lima Gumul Kediri - Meda Yusika; Sudarmiatin Sudarmiatin; A. Rosyid Al Atok (Graduate School of Universitas Negeri Malang, 2021)
Abstract: The purpose of this research development is to produce non-textbooks with the character value of the Kediri SLG relief. The product consists of student books and teacher books developed with the 4D model, namely Define, Design, Develop, and Disseminate. Product feasibility test is obtained through expert validation, and development test. The product validation test, respectively, obtained an average of 97%, 98%, and 97% that declared valid and can be used. Development testing is divided into small group trials and field trials. In a small group trial an assessment of student responses and student activity was carried out on the product. Student responses scored 98% and student activities 93%, which means that the product is very effective in learning. Then the field test consists of effectiveness tests in learning 1 to 5 obtaining an average percentage of 93% and hypothesis testing using Paired Sample T-Test with the acquisition of sig values. 0,000 <0.050, meaning the use of the product has an effect on the learning outcomes of fourth grade students. Based on a series of tests carried out, the product was declared to have met the criteria and requirements for use in the field as a supporting book.Abstrak: Tujuan penelitian pengembangan ini adalah menghasilkan buku non teks bertema nilai karakter dari relief SLG Kediri. Produk terdiri dari buku buku siswa dan buku guru yang dikembangkan dengan model 4D, yaitu define, design, develop, dan disseminate. Uji kelayakan produk diperoleh melalui uji validasi ahli dan uji pengembangan. Uji validasi produk secara berurutan memperoleh rerata sebesar 97%, 98%, dan 97% yang artinya valid dan dapat digunakan. Uji pengembangan dibedakan atas uji coba kelompok kecil dan uji coba lapangan. Pada uji coba kelompok kecil dilakukan penilaian respon siswa dan aktivitas siswa terhadap produk. Respons siswa mendapat skor 98% dan aktivitas siswa sebesar 93% yang artinya produk sangat efektif digunakan dalam pembelajaran. Kemudian uji lapangan terdiri atas uji efektivitas pada pembelajaran 1—5 memperoleh rerata persentase sebesar 93% serta uji hipotesis menggunakan uji Paired Sample t-test dengan perolehan nilai sig. 0,000<0,050, berarti penggunaan produk berpengaruh pada hasil belajar siswa kelas IV. Berdasarkan serangkaian pengujian yang dilaksanakan, produk dinyatakan sudah mencukupi kriteria dan persyaratan guna digunakan di lapangan sebagai buku penunjang.